Intercultural Experience and Identity Narratives of Chinese Doctoral Students in the UK - Ye, Lily Lei (Palgrave Studies on Chinese Education in a Global Perspective, 2018)
This book examines the identity formation and negotiation of Chinese doctoral students in the UK, and the opportunity for self-transformation this experience offers. As the largest group of international students in the English-speaking world, Mainland Chinese students encounter a range of difficulties and prospects that may be relevant to the wider international student community. Using extensive qualitative and empirical data, the author explores the narratives of eleven Chinese doctoral students at two British universities through a sociological perspective. Balancing analysis with solid theoretical framework and the voices of the students themselves, the author moves away from essentialism and 'othering', instead shining a light on the effects of globalisation, internationalisation and recent policy strategies. This volume will be of interest and value to students and scholars of comparative and international education, identity formation, intercultural communication, the sociology of education and study abroad.